Effect of Pre-Sowing Seed Treatments on Seed Yield and Quality of Soybean [Glycine max (L) Merill] - KP VAGHASIYA; JB PATEL; JR SONDARVA (Seed Research, 2026)
An investigation was carried out in kharif 2021 to evaluate the effect of pre-sowing seed treatments on seed yield and quality of soybean. The experimental materials comprising two factors, varieties (V1: GJS 3 and V2: JS 335) and pre-sowing seed treatments (S1: Control, S2: Hydration-dehydration treatment with distilled water for 8 hrs, S3: 1.5 % CaCl2 for 8 hrs. (15 ml/l), S4: 2.0 % KH2PO4 for 8 hrs. (20 ml/l), S5: 1.0 % KNO3 for 8 hrs. (10 ml/l), S6: 10 % PEG 6000 for 8 hrs. (100 ml/l), S7: 10 % Rhizobium japonicum culture for 8 hrs. (100 ml/l), S8: Seed coating with sweet flag rhizome powder @ 5 g/kg seed, S9: Seed coating with cytozyme SDM powder @ 3 g/kg seed and S10: Seed coating with neem kernel powder @ 5 g/kg seed) was carried out at Junagadh, Gujarat. The observations were recorded on seed yield per plant and its contributing traits in the field. Seed quality parameters were also measured in the laboratory conditions from the fresh seed harvested from filed experiment. Variety JS 335 showed it superiority over GJS 3 recorded higher field emergence, seed yield and its components with lower days to 50 per cent flowering, days to maturity, germination percentage, seedling length, seedling dry weight, seedling vigour index I and seedling vigour index II with low value of seed moisture content and electrical conductivity of seed leachates. Among pre-sowing seed treatments, seed coating with sweet flag rhizome powder @ 5g/kg seed recorded the maximum field emergence, seed yield and its components and quality parameters.